2005
DOI: 10.1159/000083245
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Taurine against Nicotine-Induced Oxidative Damage of Rat Urinary Bladder and Kidney

Abstract: Several studies demonstrate that taurine treatment prevents tissue damage in various models of inflammation. Experiments have shown that chronic nicotine administration caused oxidant damage in various organs by increasing lipid peroxidation products and decreasing the activity of endogenous antioxidants. The aim of this study was to investigate the effects of taurine treatment on nicotine-induced oxidative changes in rat urinary bladder and kidney and to explore the possible mechanisms of action. Male Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 38 publications
2
22
1
Order By: Relevance
“…However, Arany et al (2011) found that chronic nicotine exposure increased the extent of renal injury which may be attributed to their prolonged treatment for 4 weeks. Similarly, measurement of BUN showed no significant changes which is in contrary to the finding of Sener et al (2005) who show a significant increase in the BUN values. Interestingly, nicotine by itself produced a less profound effect on BUN than to its combination treatment with alcohol (Bekairi et al 1987).…”
Section: B a D C Econtrasting
confidence: 93%
See 1 more Smart Citation
“…However, Arany et al (2011) found that chronic nicotine exposure increased the extent of renal injury which may be attributed to their prolonged treatment for 4 weeks. Similarly, measurement of BUN showed no significant changes which is in contrary to the finding of Sener et al (2005) who show a significant increase in the BUN values. Interestingly, nicotine by itself produced a less profound effect on BUN than to its combination treatment with alcohol (Bekairi et al 1987).…”
Section: B a D C Econtrasting
confidence: 93%
“…An insignificant rise in the plasma levels of the creatinine due to nicotine treatment was observed by us what is in line with the observation of other groups (Sener et al 2005). However, Arany et al (2011) found that chronic nicotine exposure increased the extent of renal injury which may be attributed to their prolonged treatment for 4 weeks.…”
Section: B a D C Esupporting
confidence: 90%
“…Chronic NIC exposure increases ROS production in mesangial (23) and proximal tubule (25) cells in vitro. In animal models, chronic exposure to cigarette smoke or NIC significantly increased oxidative stress in the kidney and pretreatment with antioxidants prevented renal injury (9,22,32,43). These results clearly connect smoking/chronic NIC to oxidative injury.…”
Section: Discussionmentioning
confidence: 73%
“…19). Chronic exposure to NIC increases oxidative stress in the kidney (22,43), cultured proximal tubule (25), or mesangial cells (23), thus linking smoking and NIC to renal injury (23). Consequently, smoking or chronic NIC exposure might exacerbate acute renal injury through increasing oxidative stress as observed in experimental radiocontrast-induced AKI (17).…”
mentioning
confidence: 99%
“…Nicotine itself induces oxidant damage in various organs by increasing lipid peroxidation products and decreasing the activity of endogenous antioxidants [Sener et al 2005] and the higher levels of nicotine that the fetus is exposed to than the mother implies that the fetus is also exposed to higher levels of oxidants. This can readily result in an oxidant/antioxidant imbalance which can adversely impact on cell survival and thus development of organs.…”
Section: Nutrient Supplementationmentioning
confidence: 99%